Decrease of ceramides with long‐chain fatty acids in psoriasis: Possible inhibitory effect of interferon gamma on chain elongation. Issue 2 (22nd July 2021) - Kim, Bo‐Kyung; Shon, Jong Cheol; Seo, Hee Seok; Liu, Kwang‐Hyeon; Lee, Jong Won; Ahn, Sung Ku; Hong, Seung Phil
Abstract: Reportedly, decreases in fatty acid (FA) chain length of ceramide (CER) are associated with interferon‐γ (IFN‐γ), which shows increased expression in psoriasis. However, the underlying mechanism of this association remains unclear. Therefore, in this study, we aimed to clarify this association between FA chain length of CER, IFN‐γ, and the major transcriptional factors involving psoriasis. CER profiling according to FA chain length and class was performed in murine epidermis ( n  = 10 BALB/c mice topically treated with imiquimod, n  = 10 controls) and human stratum corneum (SC) ( n  = 12 psoriasis, n  = 11 controls). The expression of lipid synthetic enzymes, including elongases (ELOVLs), in murine epidermis was also measured using RT‐PCR. Furthermore, the association of IFN‐γ with various enzymes and transcription factors involved in the generation of long‐chain CERs was also investigated using in vitro keratinocyte. A significant decrease in the percentage of long‐chain CERs was observed in psoriasis‐like murine epidermis and human psoriatic SC. Additionally, the expression levels of ELOVL1, ELOVL4, and ceramide synthase3 (CerS3) were significantly decreased in psoriasis‐like murine epidermis and IFN‐γ‐treated keratinocyte. There was also a significant decrease in the expression of transcriptional factors, including peroxisome proliferator‐activated receptor (PPAR), in IFN‐γ treated keratinocyte. Thus, it could be suggested that IFN‐γ may regulate ELOVL and CerS levels by down‐regulating the transcriptional factors. Additionally, given the possible involvement of PPARs or liver X receptor agonist in the CER elongation process, they may serve as potential therapeutic agents for lengthening the CER FAs in psoriasis.